Validity and Reliability of the Turkish Version of the 8-Item Morisky Medication Adherence Scale in Patients With Type 2 Diabetes - Sayiner, Zeynel Abidin; Savaş, Esen; Kul, Seval; Morisky, Donald E. (European Journal of Therapeutics, 2023)
Objective: Diabetes mellitus (DM) is a common disorder that causes undesirable medical and economic consequences. A simple, reliable, and validated self-report instrument could provide a better understanding of non-adherence to treatment and may help identify new treatment modalities. Thus, the eight-item Morisky Medication Adherence Scale (MMAS-8) was developed. The aim of this study was to evaluate the validity and reliability of the MMAS-8 among Turkish diabetes mellitus patients. Methods: This cross-sectional descriptive study enrolled 199 patients. The Turkish translation of the Morisky-8 item scale consisted of forward translation, reconciliation, back translation, back translation review, developer review, pilot testing, and final translation. Results: Cronbach’s alpha test of internal consistency was calculated at alpha=0.890 for the eight items of the MMAS-8 scale. CFA demonstrated the scale fitted CMIN/DF=1.194, GFI=0.970, CFI=0.995, RMSEA=0.031. Poor glycemic control (HbA1c<7) was significantly higher in the low-adherence group than in the high- and medium-adherence groups (p=0.001, LR=21.79). Approximately 94% of the low-adherence group patients were in the poor glycemic control group. Conclusion: The MMAS-8 Turkish version was found to be a valid and reliable scale in diabetic patients. This self-reported scale could function as a screening tool in busy clinics to identify patients with low adherence to medication treatment. Moreover, the MMAS-8 Turkish version could help improve adherence and develop new treatment strategies.